2015
DOI: 10.1080/02508060.2015.1096110
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability in the water–energy–food nexus

Abstract: EditorialIFPRI3; CRP5; ISIEPTDPRCGIAR Research Program on Water, Land and Ecosystems (WLE

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(72 citation statements)
references
References 17 publications
(16 reference statements)
0
61
0
2
Order By: Relevance
“…In weak sustainability [29], resources are not the only focus of sustainable development, the human factor affects sustainable development either directly or indirectly because the population is the principle component in the sustainable development system and the continuum in production and consumption [30]. Since the security in water, energy, and food is interwoven with human, economic, and environmental sustainability [31,32], there is strong interdependence between the WEF-Nexus and the population system, economic system, and environmental system (Figure 1). …”
Section: Economic Implications Of Input-output Efficiencymentioning
confidence: 99%
“…In weak sustainability [29], resources are not the only focus of sustainable development, the human factor affects sustainable development either directly or indirectly because the population is the principle component in the sustainable development system and the continuum in production and consumption [30]. Since the security in water, energy, and food is interwoven with human, economic, and environmental sustainability [31,32], there is strong interdependence between the WEF-Nexus and the population system, economic system, and environmental system (Figure 1). …”
Section: Economic Implications Of Input-output Efficiencymentioning
confidence: 99%
“…Discussions are under way to improve existing governance and policy systems by adopting the WEF nexus. The improvement of existing governance includes a broad involvement and collaboration of planners and policymakers (financial, institutional, technical, and intellectual sectors) to build a responsible and supportive governance at local, national, and supranational level (Bhaduri et al, 2015). On the policy side, Gain et al (2015) suggested the integration of the existing policies of each sector, rather than creating a new exclusive policy.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it requires the participation of stakeholders to conduct international collaboration. Finally, the nexus governance should have a continuous innovation, political support, constant monitoring, and transparent governance principles to achieve sustainable development and reduce competition or conflicts (Bhaduri et al, 2015).…”
Section: Involvement Of Stakeholders and Policymakersmentioning
confidence: 99%
“…For example, they illustrate the water flows needed to irrigate land and the energy flows required for the production of ethanol. Alternatively, papers focus on the social side of the equation and discuss for instance how institutional coordination can help to establish a nexus between WEF (see e.g., Scott et al 2011;Harvey 2014;Foran 2015;Bhaduri et al 2015;Gain et al 2015;Halbe et al 2015;Biggs et al 2015;Smajgl et al 2016;Boas et al 2016). Very few articles or literature strands examine both material and social dimensions when understanding or assessing the nexus of WEF.…”
Section: The Urban Nexus: Connecting Materials and Social Flowsmentioning
confidence: 99%
“…In the quest of the nexus, there are many hurdles and complexities related to policy and decisionmaking to overcome. These may concern limitations resulting from administrative boundaries (city, regional or national scale); the scale of the management of WEF (municipal, regional or national) (Bhaduri et al 2015;Biggs et al 2015;Weitz et al 2017); and disarticulation in the policy and decision-making (Gain et al 2015). Actors in the quest of making the nexus thus constantly have to coframe sustainability related goals, co-define problems, or contest perceptions with regard to effective policy making or even what a nexus governance of WEF is like.…”
Section: Socially Driven Nexusmentioning
confidence: 99%